The effects of mergers on the formation of disc-bulge systems in hierarchical clustering scenarios - Scannapieco, Cecilia (2003)
We study the effects of mergers on the structural properties of disc-like systems by using smooth particle hydrodynamical (SPH) numerical simulations in hierarchical clustering scenarios. In order to assess the effects of mergers on the mass distributions we performed a bulge—disc decomposition of the projected surface density of the systems at different stages of the merger process. We assumed an exponential law for the disc component and the Sérsic law for the bulges. We found that simulated objects at z= 0 have bulge profiles with shape parameters n≈ 1, consistent with observational results of spiral galaxies. The complete sample of simulated objects at z= 0 and z > 0 shows that n takes values in the range n≈ 0.4–4. We found that secular evolution tends to produce exponential bulge profiles, while the fusion of baryonic cores tends to increase the n value and helps to generate the correlation between B/D and n. We found no dependence on the relative mass of the colliding objects. Our results suggest that mergers, through secular evolution and fusions, could produce the transformation of galactic objects along the Hubble sequence by driving a morphological loop that might also depend on the properties of the central galactic potential wells, which are also affected by mergers.